Speaking of God in the Realm of Aesthetics: Religion in Hölderlin - Jakob Helmut Deibl (Religions, 2023)
This article considers the work and reception of Friedrich Hölderlin with regard to the impact of German Idealism on religion. To this end, two questions must be clarified in advance: can Hölderlin, who is known primarily as a poet, also be placed in the context of German Idealism, and does his work have a significant relationship to religion? I argue that both questions should be answered in the affirmative. Ernst Cassirer’s study Hölderlin und der deutsche Idealismus (1918/19) clearly laid the foundation for appreciating Hölderlin’s place within German Idealism, and the question of God is a leitmotif of Hölderlin’s entire oeuvre. I seek to trace Hölderlin’s influence on understanding religion in three steps: First, I want to show that Hölderlin, in a critical continuation of Kant, does not consider religion solely within the matrix of practical reason, but brings into play the dimension of aesthetics. By situating religion in relation to the two focal points of ethics and aesthetics, a fundamental question of the philosophy of religion is addressed. Second, I employ several examples to show the various conceptions of the divine that the poet elucidates and juxtaposes in his work (Christian motifs, Greek mythology, pantheistic concepts, etc.). This leads to a philosophy of religion that is not determined by dogmatic boundaries. Third, I point out how religion plays a major role in the reception of Hölderlin.